Design of MAC protocol and performance analysis for heterogeneous nodes separating CRSN - Deyue MENG; Errong PEI; Youlin HUANG (Dianxin kexue)
Cognitive wireless sensor network (CRSN) is a new type of network that introduces cognitive radio (CR) technology into traditional WSN,and has certain application value and developmental prospect.However,the additional energy consumption,processing requirements and its high cost implementation have hindered its further development and application.Based on this,transfering cognitive functions to another nodes——cognitive nodes which have ability of processing and collecting energy was proposed.The cognitive nodes were deployed with the ordinary sensor nodes according to the certain proportion.They form a new type of network——heterogeneous node CRSN (HT-CRSN).The new network can improve network performance and reduce the deployment cost.Then a work schedule which can be applied to this kind of heterogeneous node sensor networks and a series of feasible MAC protocols was proposed.The analysis of the proposed MAC protocol proves that energy consumption can be balanced by adjusting the deployed ratio of the two kinds of heterogeneous nodes and the network life cycle is improved.